Isolasi dan Identifikasi Kapang Pelarut Fosfat dari Fosfat Guano Gua Pawon - Anggita Rahmi Hafsari (Universitas Islam Negeri Mataram, 2017)
The purpose of this study was to isolate and identify phosphate solubilizing Fungi from phosphate guano in Pawon Cave, Karst area, Citatah, West Java. The research design was descriptive. The data obtained were presented descriptively based on macroscopic and microscopic morphological characteristics and the result of qualitative phosphate capability screening on pikovskaya medium. The results showed that there were five isolates in the phosphate guano in Pawon Cave. Karst area, which were Penicillium sp. PF1, Aspergillus sp. PF2, Aspergillus sp. PF3, Mycelia sterilia, and Mucor sp. Based on the screening test, there were two isolates which could solubilize the phosphate, Aspergillus sp. PF3 and Mucor sp.